Can Work Be Meaningful Under Algorithmic Management?: A MacIntyrean Perspective - García Ruiz, Pablo (Business ethics quarterly, 2026)
Algorithmic management is deeply changing the way work is performed and the interaction between managers and workers in organizations. It also heavily affects the conditions for meaningful work highlighted by existing literature. Therefore, organizations need an appropriate framework to enable meaningful work when adopting algorithmic management systems. This article presents a normative study of the conditions for work to be meaningful in this new scenario. To fulfil this purpose, it adopts a MacIntyrean approach, according to which work is meaningful when it embodies practice-like characteristics. The article identifies the main threats of algorithmic management and characterizes the normative conditions organizations should meet to enable meaningful work. In addition, the article explores the strategies of resistance that workers use to live up to the standards of meaningful work when organizations are not capable or willing to provide those conditions.